Sustainable Tourism Practices in High-Traffic Destinations : A Case Study of Wineries with Sustainable Practices - Arguelles, Nicole Hannah; Kvítková, Zuzana; Kučera, Dušan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This study investigates sustainable tourism practices in high-traffic wineries, aiming to understand how they manage environmental, social, and economic impacts amidst operational and external pressures. A qualitative multi-case study approach was used and data was collected through semi-structured interviews from five European wineries (Czech Republic, Slovakia, Italy, France) and thematic analysis was employed. The study identified five core interconnected themes: Foundational Environmental Stewardship, Quality-driven Economic Viability, Strategic Wine Tourism, Stakeholder Engagement and Collaboration, and Operational and External Pressures, all framed within an overarching concept of Sustainable Development and Systems Thinking. Results indicate that intrinsic management motivation, long-term vision, and focus on quality are crucial for successful sustainability integration, with environmental stewardship directly linked to economic viability and effective stakeholder engagement key to navigating complexities.
Vedoucí práce: Zuzana Kvítková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses